Simulation calculation and comparative analysis of three-dimensional temperature field of ultra high voltage through wall bushing under different current carrying capacity - Yunfei Shi (Elsevier, 2021)
As the key equipment of UHV transmission and transformation line, UHV bushing needs to carry the ultra-high voltage and large current of UHV power system at the same time. When the operating temperature of UHV bushing is too high, the operation failure rate will increase significantly, which will affect the stability and safety of UHV transmission line. Therefore, it is particularly important to analyze the temperature field characteristics of UHV bushing. This paper takes UHV bushing as the research object. The finite element software is used to calculate the electro thermal coupling. The three-dimensional thermal field distribution characteristics of UHV bushing are simulated and analyzed. This paper analyzes the influence of eddy current on the temperature distribution of UHV bushing under operation condition, and discusses the influence degree of eddy current on the temperature distribution of bushing, which provides an important basis for the temperature distribution, structure improvement and operation maintenance of bushing.